ASSESSMENT INDICATORS OF THE DEVELOPMENT OF SOCIAL COMPETENCES IN STUDENTS - Nurjamal Jarkurganovna Umirova (Western European Studies, 2024)
The article talks about the indicators of the development of social competences in students.
Keywords: Student; social; competence; development